Evaluation of the impact of the implementation of accountability accounting and logistics management on company performance (case study at PT. Javanusa Multi Cargo Semarang City) - Sumaroh, Sumaroh; Lutfi, Lisda Samara; Suhantoro, Suhantoro (SEAN Institute, 2024)
Research with the problem